Understanding the Contribution of Internal Audit to the Governance of Moroccan Local Authorities: Organizational and Contextual Dynamics - SIMOU, Zineb; DAOUI, Driss (Revue Internationale des Sciences de Gestion, 2026)
This article analyzes the contribution of internal audit to strengthening the governance of Moroccan territorial authorities in a context marked by advanced regionalization and the modernization of public management. Based on an exploratory qualitative approach grounded in semi-structured interviews conducted with key institutional actors, the study highlights that the impact of internal audit on local governance cannot be understood in a mechanical or strictly normative manner. The findings show that internal audit constitutes a structuring lever of governance, whose effectiveness depends on intermediate organizational mechanisms, particularly organizational climate and the optimization of internal processes, as well as contextual factors such as the leadership of elected officials and citizen engagement. On this basis, the research proposes a conceptual model integrating direct relationships, mediating mechanisms, and moderating effects, thereby contributing to a more refined and contextualized understanding of the conditions under which internal audit becomes effective in the governance of Moroccan territorial authorities.